2005
DOI: 10.1532/ijh97.a10418
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Gene Polymorphism and Susceptibility to Childhood Acute Lymphoblastic Leukemia in a Chinese Population

Abstract: Cyclin D1 is a key protein involved in cell cycle regulation. A common A870G single nucleotide polymorphism in exon 4 of the cyclin D1 gene (CCND1) has an effect on the transcription of 2 different cyclin D1 messenger RNAs. Correlation between genetic polymorphism of A870G of CCND1 and clinical outcome among patients with acute lymphoblastic leukemia (ALL) has been reported. However, the effect on ALL occurrence remains unclear. To examine the genotypic frequency of CCND1 polymorphism, we performed a case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Hou et al (2005) found that this SNP increased the risk of acute lymphoblastic leukemia under the recessive model, and Bedewy et al (2013) reported that the AA genotype significantly increased the risk of acute lymphoblastic leukemia compared with the GG genotype. The authors of the latter study also found that the CCND1 G870A polymorphism did not influence the susceptibility to mantle-cell lymphoma and chronic lymphocytic leukemia (Howe and Lynas, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al (2005) found that this SNP increased the risk of acute lymphoblastic leukemia under the recessive model, and Bedewy et al (2013) reported that the AA genotype significantly increased the risk of acute lymphoblastic leukemia compared with the GG genotype. The authors of the latter study also found that the CCND1 G870A polymorphism did not influence the susceptibility to mantle-cell lymphoma and chronic lymphocytic leukemia (Howe and Lynas, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the numerous relevant epidemiologic studies investigating the relationship between the CCND1 G870A variant and hepatocellular carcinoma (Zhang et al, 2002;Pakakasama et al, 2004;Akkiz et al, 2010;Hu et al, 2014) or leukemia (Howe and Lynas, 2001;Hou et al, 2005;Bedewy et al 2013) have yielded conflicting and controversial results. There has been no systematic or quantitative assessment of the published findings on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The other two (47,48), with a total weighted contribution of 15.7%, have powers of 48.6% and 9.5%, respectively. By contrast, effect in genitourinary cancers may be attributed to four studies (52,53,55,56) with statistical powers that ranged from 57.6 to 64.6 and a total weighted contribution of 84.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity was explored using subgroup analysis (10) with ethnicity (Asians and Caucasians) and cancer types. We have classified the cancer types in nine different categories including breast (13)(14)(15)(16)(17)(18)(19), colorectal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), gynecologic [ovarian (35), cervical (36), and endometrial (37)], digestive tract [oral (38)(39)(40), esophageal (41)(42)(43)(44), and stomach (45,46)], blood-related [acute lymphoblastic leukemia (47), mantle cell lymphoma (48), and non-Hodgkin's lymphoma (49)], genitourinary [bladder (50)(51)(52)(53), prostate (54,55), and kidney (56)], lung (57)(58)(59)…”
Section: Methodsmentioning
confidence: 99%
“…Manual search of references did not cite in any additional article. Finally, a total of 9 publications including 10 case-control studies met the inclusion criteria for the meta-analysis (including a total of 6085 leukemia and non-Hodgkin lymphoma cases and 5460 controls) (Howe et al, 2001;Hou et al, 2005;Wang et al, 2006;Morton et al, 2009;Fernberg et al, 2010;Rong et al, 2010;Wang et al, 2011;Qian et al, 2012;Bedewy et al, 2013). There were 6 studies of leukemia (containing 4 of ALL, 1 of CLL and 1 of CML), and 4 of non-Hodgkin lymphoma.…”
Section: Eligible Studiesmentioning
confidence: 99%